Exploring the Impact of The NEST Collaborative's Remote Social Intervention on Feelings of Depression and Isolation. (September 2022) - Nolan, Ryan W.; Friedman, Sarah; Carson, Jennifer; Gibb, Zebbedia; Acklin, Casey; Reed, Peter S.
Early evidence of remote, volunteer-led social support interventions to reduce social isolation in older adults has been encouraging; however, evaluation data on outcomes related to social isolation associated from these interventions is scarce. Here, we share programmatic details of a novel, statewide initiative, called the NEST Collaborative, rolled out to meet immediate emotional, informational, and instrumental needs of older adults in Nevada during the COVID-19 pandemic. The evaluation included 31 older adults participating in weekly one-to-one empathy-based phone calls with multi-generational volunteers seeking to enhance participants' social networks through meaningful friendships. The calls were associated with programmatically meaningful, though not statistically significant, improvements in modified Hawthorne Friendship Scale and PHQ-2 Depression Scale scores over two waves of survey responses. These results suggest that social isolation and depression among older adults decreased among our sample over a period of increased isolation and mental health burden across the general population. With the potential for sustained impact in reducing social isolation over time, remote social support programs, such as the NEST Collaborative, may have persistent value long-term, beyond time-limited crisis response contexts.